Hypokalaemia and refractory asystole complicating diabetic ketoacidosis, lessons for prevention. (5th December 2012) - Abdulaziz, Salman; Dabbagh, Ousama; Al Daker, Mohamed Ousama; Hassan, Imad
Summary: We report a unique case of diabetic ketoacidosis in which a relatively low potassium level on admission was associated with consequent life-threatening and refractory arrhythmia secondary to inappropriate use of intravenous insulin and bicarbonate therapy. The latter was reversed by rapid bolus potassium injection. Although we do not advocate this approach in every case, we emphasise that a bolus injection of potassium may be life saving in such cases. The lessons from this case have led to multidisciplinary meetings and modification of the institute's diabetic ketoacidosis clinical pathway.